If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + -26 = -44 Reorder the terms: -26 + y = -44 Solving -26 + y = -44 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '26' to each side of the equation. -26 + 26 + y = -44 + 26 Combine like terms: -26 + 26 = 0 0 + y = -44 + 26 y = -44 + 26 Combine like terms: -44 + 26 = -18 y = -18 Simplifying y = -18
| 35+x=3 | | 21x^4+102x^3y-15x^2y^2=0 | | 8y+(-2x)-4x+1-4y+8= | | (3x^2)-5x-8=0 | | 3x+y+4+2x+3y+16=90 | | 5s-18-4(s)= | | 24=y-11 | | 15a^2-34a+15=0 | | x=5+0.75y | | 2.65+3.1x=5.83x | | 5-15.8=24.6 | | (2x^2)+5x+3=0 | | 8y-5y+9=3y+y-1 | | -10=6+w/2 | | 2x+8=30 | | -10=6w/2 | | 6y+y=84 | | 13x-31=2x-9 | | 1.41(4x-1)+3.14x=0 | | 9x+8=171 | | 10y^3-25y^2-125y=0 | | -81=9x | | -9(x+4)+9=-27 | | 11x+19x-6+2=8x+2-6 | | 4x+2=76 | | -2(x+3)=1-2x | | 2x(6x+5)=(3x-2)(4x+1) | | 1.5(6-x)=1.3(4-x) | | 0.10(x+200.00)=55 | | x^3-2x^2+3x-2=0 | | 7x+9=91 | | 3(x+3)+4x=15-2x+13 |